Numerical study on the plastic deformation behavior of AZ31 magnesium alloy under different loading conditions - Yuyu Li; Bowen Yang; Tingzhuang Han; Zhibing Chu; Chun Xue; Qianhua Yang; Xiaodong Zhao; Hong Gao (Materials Research Express, 2021)
Based on the stress characteristics of the instantaneous cross-section deformation of the wall reducing section during the cold rolling of two-roll Pilger pipes, the rectangular samples with 0° and 90° to the extrusion direction (ED) were cut from the extruded AZ31 magnesium alloy bar for 3% pre-deformation test to simulate its stress state equivalently. The sample was then cut from the pre-deformed sample by wire cutting for secondary compression, and the sample that is not pre-deformed is selected. The mechanical behavior and texture evolution of AZ31 magnesium alloy under different loading conditions were respectively studied by EBSD experiment and VPSC simulation. Results show that the true stress–strain curve and texture evolution characteristics of AZ31 magnesium alloy during the secondary compression process are in good agreement with the prediction of the VPSC model. The secondary compression behavior can be effectively explained by the relative activity of the deformation modes. The pre-deformation in the ∥ED (⊥ED) direction is conducive to the shift of the pole density of the {0001} basal surface texture to the positive and negative directions of the ED (TD). The pre-deformed sample exhibits a higher yield strength than the non-pre-deformed sample in the same loading direction. The high ductility of magnesium alloys can be achieved by activating pyramidal 〈c + a〉 slippage.